Renal Cell Carcinoma in A Patient with Kartagener Syndrome: First Case Report in English Language - Erkin Sağlam; Akif Türk; Ahmet Selimoğlu; Mehmet Kutlu Demirkol; Nertila Poci Sağlam; Aydın Özgül (Journal of Urological Surgery, 2015)
Cardiac and pulmonary anomalies are common among patients with situs inversus totalis. Renal anomalies, including renal agenesis, dysplasia, hypoplasia, ectopia, polycystic kidney, and horseshoe kidney have been reported. We report a case of renal cell carcinoma in a patient with situs inversus totalis (SIT). Our case represents the fourth case report of renal cell carcinoma in a patient with situs inversus totalis and to the best of our knowledge this is the first report in English language. Due to the higher frequency of cardiac, pulmonary, renal, and vascular anomalies the management of patients with situs inversus and urologic disease requires careful preoperative evaluation.